The Effectiveness of Storytelling Method To Increase Language Development In Early Childhood - Ryan Hidayat Rafiola; Dian Anggraini; Vivi Nila Sari (Universitas of Muhammadiyah Makassar, 2022)
Language is an effective medium for children in establishing social communication. Children's language development is a combination of social interaction, emotional development, intellectual ability, as well as physical and motor development. Early education has an important role in developing children's potential. Teachers must be able to choose what methods are effective for developing language in children. This study aims to determine the effect of using the storytelling method on the development of language and language skills of early childhood. The research method used is an associative research type. Respondents in this study amounted to 30 children. Data collection techniques used by observation techniques, the research instrument used was an observation sheet in the form of an assessment rubric. The data analysis technique used a simple linear regression test. The results of the simple linear regression test showed that there was an effect of using the storytelling method on the development and language skills of early childhood. Children are able to speak fluently, word choice and sentence structure are also very good. The storytelling method can improve language development and skills in early childhood. Using the storytelling method can help improve language development and skills in early childhood.